INDUSTRI ASURANSI JIWA DIGITAL DALAM PERSPEKTIF HUKUM POSITIF INDONESIA - Sherlly Febrianty; Helena Primadianti Sulistyaningrum (Sriwijaya Journal of Private Law, 2024)
As the world develops, technology is increasingly developing. Many things can be used as new business opportunities for companies, including insurance companies. Article 1 number 1 of Law Number 40 of 2014 concerning Insurance reads, "Insurance is an agreement between two parties, namely an insurance company and a policyholder". In its function, the digital insurance industry can be used to increase public understanding and awareness of the importance of insurance and self-protection. It is known that not all people are digitally literate and there are still remote areas that even still lack technology, so we need to know the impact on the accessibility of digital insurance services for the community. Furthermore, the normative legal analysis method is used as a material for analyzing data, with discussions and explanations based on norms and doctrines or literature materials related to the material under study. Thus, there are results from the research that the digital insurance industry can increase operational efficiency and provide faster service to customers. Through the digital insurance industry, the digital life insurance industry, which has shown significant development in recent years, allows for transparency and consumer literacy in order to understand digital life insurance. Legal protection for digital insurance consumers requires safeguarding trust and ensuring.